Maturing research data services and the transformation of academic libraries - Cox, Andrew M; Kennan, Mary Anne; Lyon, Liz; Pinfield, Stephen; Sbaffi, Laura (Journal of documentation, 2019)
Purpose A major development in academic libraries in the last decade has been recognition of the need to support research data management (RDM). The purpose of this paper is to capture how library research data services (RDS) have developed and to assess the impact of this on the nature of academic libraries. Design/methodology/approach Questionnaire responses from libraries in Australia, Canada, Germany, Ireland, the Netherlands, New Zealand, the UK and USA from 2018 are compared to a previous data set from 2014. Findings The evidence supports a picture of the spread of RDS, especially advisory ones. However, future ambitions do not seem to have seen much evolution. There is limited evidence of organisational change and skills shortages remain. Most service development can be explained as the extension of traditional library services to research data. Yet there remains the potential for transformational impacts, when combined with the demands implied by other new services such as around text and data mining, bibliometrics and artificial intelligence. A revised maturity model is presented that summarises typical stages of development of services, structures and skills. Research limitations/implications The research models show how RDS are developing. It also reflects on the extent to which RDM represents a transformation of the role of academic libraries. Practical implications Practitioners working in the RDM arena can benchmark their current practices and future plans against wider patterns. Originality/value The study offers a clear picture of the evolution of research data services internationally and proposes a maturity model to capture typical stages of development. It contributes to the wider discussion of how the nature of academic libraries are changing.